2000
DOI: 10.1021/ja992501u
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change of the Mn Cluster during the S2→S3 State Transition of the Oxygen-Evolving Complex of Photosystem II. Does It Reflect the Onset of Water/Substrate Oxidation? Determination by Mn X-ray Absorption Spectroscopy

Abstract: The oxygen-evolving complex of Photosystem II in plants and cyanobacteria catalyzes the oxidation of two water molecules to one molecule of dioxygen. A tetranuclear Mn complex is believed to cycle through five intermediate states (S 0 -S 4 ) to couple the four-electron oxidation of water with the one-electron photochemistry occurring at the Photosystem II reaction center. We have used X-ray absorption spectroscopy to study the local structure of the Mn complex and have proposed a model for it, based on studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
189
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(221 citation statements)
references
References 85 publications
(247 reference statements)
30
189
0
2
Order By: Relevance
“…Comparison of the integrated areas showed that urea or CaCl 2 treatments removed 82 and 92% of native PsbO, respectively. Reconstitution with 12 C-or 13 C-PsbO to urea-PSII gave quantitative (120%) rebinding. This analysis is consistent with previous results for a different PSII preparation (24,79).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparison of the integrated areas showed that urea or CaCl 2 treatments removed 82 and 92% of native PsbO, respectively. Reconstitution with 12 C-or 13 C-PsbO to urea-PSII gave quantitative (120%) rebinding. This analysis is consistent with previous results for a different PSII preparation (24,79).…”
Section: Methodsmentioning
confidence: 99%
“…Flash excitation can be coupled with spectroscopic techniques to identify structural changes associated with each S state transition (for examples, see Refs. [12][13][14][15].…”
Section: And References Therein)mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the structure of the cluster changes dramatically upon S 3 -state formation (Liang et al 2000;Haumann et al 2005) and is also different in the S 0 state Haumann et al 2005). This structural flexibility may be key to the catalytic activity of the WOC.…”
Section: Introductionmentioning
confidence: 99%